War in a Time of Peace : Bush, Clinton, and the Generals - Halberstam, David (New York Scribner, 2001)
"More than twenty-five years ago Halberstam told the riveting story of the men who conceived and executed the Vietnam War. Today the author has written another chronicle of Washington politics, this time exploring the complex dynamics of foreign policy in post-Cold War America." "Halberstam evokes the internecine conflicts, the untrammeled egos, and the struggles for dominance among the key figures in the White House, the State Department, and the military. He shows how the decisions of men who served in the Vietnam War - such as General Colin Powell and presidential advisers Richard Holbrooke and Anthony Lake - and those who did not have shaped American politics and policy makers (perhaps most notably, President Clinton's placing, for the first time in fifty years, domestic issues over foreign policy)."--Jacket.
Include Index
Keywords: Vietnam War (1961-1975) -- Influence (Literary, artistic, etc.) -- Military Policy -- Diplomatic Relations